Bridging the gaps: interoperability for language engineering architectures using GrAF. - Ide, Nancy; Suderman, Keith (Language Resources & Evaluation, 2012)
This paper explores interoperability for data represented using the Graph Annotation Framework (GrAF) (Ide and Suderman, ) and the data formats utilized by two general-purpose annotation systems: the General Architecture for Text Engineering (GATE) (Cunningham et al., ) and the Unstructured Information Management Architecture (UIMA) (Ferrucci and Lally in Nat Lang Eng 10(3-4):327-348, ). GrAF is intended to serve as a 'pivot' to enable interoperability among different formats, and both GATE and UIMA are at least implicitly designed with an eye toward interoperability with other formats and tools. We describe the steps required to perform a round-trip rendering from GrAF to GATE and GrAF to UIMA CAS and back again, and outline the commonalities as well as the differences and gaps that came to light in the process.